Analysis of chippaux smirak index on dynamic balance scores - Senol, Deniz; Toy, Seyma; Bilge, Damla; Ozdemir, Beyza; Ozbag, Davut (Annals of Medical Research, 2021)
Aim: The aim of this study is to examine whether Chippaux Smirak Index (CSI) calculated from footprint and measurements taken from foot have an effect on balance scores. Materials and Methods: 61volunteers (25 males, 36 females) between the ages of 18 and 24 were included in our study and 122 feet were measured. Footprints of the participants were taken by using Harris imprint. Footprints were scanned, the parameters were measured with Digimizer program and CSI was calculated. Metatarsal foot width (MFW), maximum metatarsal foot width (MMFW), length of the foot (LoFA), heel width (HW) and foot length (FL) taken from footprints were measured. Individuals with CSI >62.70% were considered as flatfooted and excluded from the study. Dynamic balance measurements were made with Biodex Balance System (BBS) (Biodex Medical Systems, Shirley, 2000, New York). Overall (OA), anterior-posterior (AP) and medial-lateral (ML) dynamic balance assessments of the participants were made with eyes open. Results: According to Mann Whitney U analysis results, statistically significant difference was found between MFW, MMFW, LoFA, HW and FL parameters of men and women in both feet (p0.05). It was found that OA, AP and ML balance scores had a statistically significant difference between men and women for dynamic balance (p0.05). According to Sperman Rho correlation analysis, a positive correlation was found between weight and body mass index (BMI) and balance scores in men and women. It was found that there was no significant correlation between CSI and balance scores. Conclusion: As a conclusion, while no association was found between weight and BMI and CSI, a positive correlation was found between weight and balance scores. We believe the fact that women have lower BMI gives them an advantage in terms of balance scores. In addition, it was found as a result of this study that there was no association between CSI and balance scores. We believe that our study will have an important place in literature and be a guide since we compared both genders.
Keywords: Chippaux smirak index; dynamic balance; foot; pes planus